Exploration targeting in porphyry Cu systems using propylitic mineral chemistry: a case study of the El Teniente deposit, Chile - Wilkinson,JJ; Baker,MJ; Cooke,DR; Wilkinson,CC (Economic Geology, 2020)
The mineral chemistry of epidote and chlorite from the propylitic halo at El Teniente, in samples collected at distances up to 6.6 km from the deposit center, was determined by microprobe and laser ablation-inductively coupled plasma-mass spectrometry. Results show that both minerals systematically incorporated a range of trace elements that define a much larger footprint to the system than is easily recognized using conventional means such as whole-rock geochemistry. Apart from Fe and Mg in chlorite, there is no significant control of mineral chemistry by bulk-rock composition. For chlorite, geothermometry temperatures and Ti and V concentrations are high proximal, whereas Li, As, Co, Sr, Ca, and Y are low proximal and elevated in distal positions. Ratios of these elements define gradients toward ore varying over three to five orders of magnitude. The proximal-high Ti content is thought to reflect crystallization temperature, whereas proximal-low signatures are believed to characterize elements that are relatively fluid mobile in the inner parts of the propylitic halo in the presence of mildly alkaline to mildly acidic and oxidized fluids so that they are not incorporated into crystallizing chlorite, despite being generally compatible within the mineral structure. These elements begin to substitute into chlorite in the distal parts of the propylitic halo where fluids are largely rock buffered in terms of major element chemistry. In epidote, As defines a broad proximal low and is generally elevated at distances of at least 3 km from the edge of the ore shell. Zinc, La, Yb, Y, and Zr in epidote, among others, appear to define a geochemical shoulder that surrounds the deposit. These patterns are broadly similar to those observed in previous work at Batu Hijau and in the Baguio district, suggesting that these minerals behave consistently in porphyry systems and can therefore provide useful exploration tools within propylitic green rocks.